Recent Advances on Study of Liquefaction and Time to Failure of Sandy Subsoil - Fadzil, Mat Yahaya; Namdar, Abdoullah (Electronic Journal of Geotechnical Engineering, 2014)
The unacceptable nonlinear force on subsoil results in unallowable settlement, deformation and failure of soil foundation. The simulation of dynamic force propagation in saturated sand has been done by several researchers. The dynamic force induces pore water pressure and causes dynamic liquefaction in sandy subsoil. The characteristics of dynamic force along with the mechanical properties of soil are responsible for magnitude of dynamic liquefaction and time to failure of soil . In this paper, the effect of dynamic force propagation and dynamic pore water pressure on liquefied sand in associate to soil mechanical properties has been evaluated. To mitigate differential settlement of footing, a simple sandy semi-confined column has been proposed. The outcome of study has been revealed near realistic behavior of liquefaction and time to failure of footing.